THE RIGHT OF CITATION AND CITATION IN THE CASE OF DOCTORAL THESES. CITATION RULES. CITATION SYSTEMS USED - Andrei-Cristian ȘTEFAN (Challenges of the Knowledge Society)
The right of citation in doctoral theses is an essential aspect of academic research and knowledge development in various fields. This fundamental concept allows PhD students to support their arguments, validate their hypotheses and strengthen their academic contribution by referring to the works and ideas of other authors. In this article, we aim to explore the role and importance of citation rights in the context of PhD theses. The right of citation serves as a basis for building an academic dialogue between the author and the scientific community. By referring to previous work, PhD students demonstrate that they know their field of study and that they incorporate its contributions into their own research. This strengthens the credibility and relevance of the PhD thesis within the academic community. The right of citation ensures compliance with academic ethics and prevention of plagiarism. By highlighting the sources used and giving proper credit to the original authors, PhD students demonstrate academic integrity and respect for the work of others. This practice promotes transparency and collaboration in research, fundamental to scientific progress and maintaining high academic standards. In addition, the citation right contributes to the development of a solid knowledge base in the field. By connecting with previous work, PhD theses situate their contribution in the existing context and can identify gaps or opportunities for future research. Thus, this citation and referencing process is an engine of academic progress, encouraging innovation and the continuous development of knowledge. Thus, the right of citation is a fundamental pillar of doctoral theses, having multiple roles and importance in the context of academic research. By following this principle, PhD students contribute to building and consolidating knowledge in their areas of expertise, promoting academic ethics and advancing the frontiers of human knowledge.